Enforcing Human Rights of Palestinians in the Occupied Territory - Qandeel, Mais (sui generis, 2018)
"The situation in Palestine has influenced the deployment of international human rights law and international humanitarian law. The impact of longterm Israeli occupation and the rule of the Palestinian Authority in the Occupied Territory is multifaceted. Despite the various research on Palestine, human rights, and the rule of law, few studies have been conducted on the enforcement mechanisms of human rights in Palestine. This study examines the applicability of international human rights and humanitarian laws as well as domestic laws to assess the contribution of these directives in protecting the fundamental human rights of Palestinians in the Occupied Territory. It conducts an in-depth case study of three basic rights: the right to movement, the right to property, and the right to equality and non-discrimination in the Occupied Territory. The study further examines the role of the Palestinian High Court of Justice and the Israeli Supreme Court in implementing domestic and international laws. In this regard, the study examines the major laws which are invoked, in certain circumstances, to limit the ability of Palestinians to confiscate, expropriate, and destruct their private property, and to implement discriminatory practices against them. The study further examines whether the available international and domestic mechanisms are effective, and if not, it suggests modifications upon which a functional national and international system could be built. The findings of the research demonstrate that international human rights treaties and international humanitarian law conventions are de facto and de jure applicable in the Occupied Territory. As a result of the aforementioned in-depth study cases, it can be concluded that human rights violations against Palestinians in the Occupied Territory are committed by the Palestinian Authority and the Israeli government. In addition, the Palestinian and the Israeli judiciaries have failed to grant Palestinians reasonable protection or a just remedy, and they are dysfunctional and politically driven. The study concludes with a proposal for new mechanisms for Palestinians to redress human rights violations. The further outcomes of this study argue that neither international human rights nor humanitarian law guarantee full protection for Palestinians. Hence, the implication of the findings indicates that the regulations of international human rights and humanitarian laws, which were made by the powers of the nineteenth century with their colonial provisions, might not fit to the present complications of the current challenges to international law in Palestine. The goal is to promote a re-thinking approach to the employment of human rights to serve all people in an efficient and well-organized system. The scope of this study is not meant to grant Palestinians favorable treatment in the multilateral international system, but to achieve just and successful remedies for victims of human rights violations."